CBP22, a Novel Bacteriocin Isolated from Clostridium butyricum ZJU-F1, Protects against LPS-Induced Intestinal Injury through Maintaining the Tight Junction Complex - Tenghao Wang; Jie Fu; Xiao Xiao; Zeqing Lu; Fengqin Wang; Mingliang Jin; Yizhen Wang; Xin Zong (Mediators of Inflammation)
A novel bacteriocin secreted by Clostridium butyricum ZJU-F1 was isolated using ammonium sulfate fractionation, cation exchange chromatography, affinity chromatography, and reverse-phase high-performance liquid chromatography (RP-HPLC). The bacteriocin, named CBP22, contained 22 amino acids with the sequence PSAWQITKCAGSIAWALGSGIF. Analysis of its structure and physicochemical properties indicated that CBP22 had a molecular weight of 2264.63 Da and a +1 net charge. CBP22 showed activity against E. col K88, E. coli ATCC25922, and S. aureus ATCC26923. The effects and potential mechanisms of bacteriocin CBP22 on the innate immune response were investigated with a lipopolysaccharide- (LPS-) induced mouse model. The results showed that pretreatment with CBP22 prevented LPS-induced impairment in epithelial tissues and significantly reduced serum levels of IgG, IgA, IgM, TNF-α, and sIgA. Moreover, CBP22 treatment increased the expression of the zonula occludens and reduced permeability as well as apoptosis in the jejunum in LPS-treated mice. In summary, CBP22 inhibits the intestinal injury and prevents the gut barrier dysfunction induced by LPS, suggesting the potential use of CBP22 for treating intestinal damage.